Fates of Intracellular and Extracellular Antibiotic Resistance Genes in Full Scale Waste Stabilization Pond Systems - Karina, Immanuela; Rahmatika, Iftita; Priadi , Cindy Rianti (Al-Makki Publisher, 2025)
Waste stabilization ponds (WSP) are conventional wastewater treatment technologies that utilize biological processes and have become key hotspots for the proliferation of antibiotic resistance genes (ARGs). During the wastewater treatment process, bacterial inactivation may release ARGs into the environment, with two primary phases of presence: intracellular (iARGs) and extracellular (eARGs). The objective of this study was to assess the abundance and removal efficiency of ARGs during the WSP process, and to explore the correlation between ARGs, total bacterial populations, and integron 1 (intl1) as a marker for horizontal gene transfer. The results showed that raw wastewater had iARGs abundance ranging from 4.69×10^5 to 5.99×10^6 gene copies/ml, and eARGs from 5.91×10^3 to 1.04×10^5 gene copies/ml. After treatment through the WSP, intracellular ARGs, intl1, and 16S rRNA genes were reduced by 0.20 to 1.73 logs, while extracellular ARGs were removed by 0.05 to 0.79 logs. Interestingly, intl1 and 16S rRNA genes showed amplification at the outlet of the wastewater treatment plant by -0.21 and -0.87 logs, respectively. The study revealed that the relative abundance of ARGs was higher in the extracellular phase, with iARGs and eARGs showing values from 7.75×10^-5 to 4.52×10^-2 and 1.33×10^-4 to 1.58×10^-1, respectively. A significant positive correlation was observed between ARGs and the total bacterial population, as well as with intl1, indicating the potential for co-occurrence and horizontal gene transfer in the microbial community within wastewater. This research highlights the environmental implications of ARGs persistence and proliferation in wastewater treatment processes, offering insights into the management of ARGs in wastewater treatment systems.